Coumarin Metabolism, Toxicity and Carcinogenicity: Relevance for Human Risk Assessment - Lake, B.G (Food and Chemical Toxicology, 1999)
The metabolism, toxicity and results of tests for carcinogenicity have been reviewed with respect to the safety for humans of coumarin present in foodstuffs and from fragrance use in cosmetic products. Coumarin is a natural product which exhibits marked species differences in both metabolism and toxicity. The majority of tests for mutagenic and genotoxic potential suggest that coumarin is not a genotoxic agent. The target organs for toxicity and carcinogenicity in the rat and mouse are primarily the liver and lung. Moreover, the dose–response relationships for coumarin-induced toxicity and carcinogenicity are non-linear, with tumour formation only being observed at high doses which are associated with hepatic and pulmonary toxicity. Other species, including the Syrian hamster, are seemingly resistant to coumarin-induced toxicity. There are marked differences in coumarin metabolism between susceptible rodent species and other species including humans. It appears that the 7-hydroxylation pathway of coumarin metabolism, the major pathway in most human subjects but only a minor pathway in the rat and mouse, is a detoxification pathway. In contrast, the major route of coumarin metabolism in the rat and mouse is by a 3,4-epoxidation pathway resulting in the formation of toxic metabolites. The maximum daily human exposure to coumarin from dietary sources for a 60-kg consumer has been estimated to be 0.02 mg/kg/day. From fragrance use in cosmetic products, coumarin exposure has been estimated to be 0.04 mg/kg/day. The total daily human exposure from dietary sources together with fragrance use in cosmetic products is thus 0.06 mg/kg/day. No adverse effects of coumarin have been reported in susceptible species in response to doses which are more than 100 times the maximum human daily intake. The mechanism of coumarin-induced tumour formation in rodents is associated with metabolism-mediated, toxicity and it is concluded that exposure to coumarin from food and/or cosmetic products poses no health risk to humans.